2009
DOI: 10.1038/nature08534
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic reversion of post-implantation epiblast to pluripotent embryonic stem cells

Abstract: The pluripotent state, which is first established in the primitive ectoderm cells (PE) of blastocysts, is lost progressively and irreversibly during subsequent development 1 . For example, development of postimplantation epiblast from PE involves significant transcriptional and epigenetic changes, including DNA methylation and X inactivation 2 , which creates a robust epigenetic barrier and prevents their reversion to a PE-like state. Epiblast cells are refractory to leukaemia inhibitory factor (LIF)-STAT3 sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
371
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(383 citation statements)
references
References 34 publications
10
371
1
1
Order By: Relevance
“…In particular, both cell types are maintained by the same extrinsic signals, namely, activin/ nodal and FGF2 signaling. Recent studies have demonstrated that EpiSCs, which are more advanced developmentally than mESCs, can be induced to revert to mESC-like cells [41,42,[49][50][51]. FAB-SCs are generated from the preimplantation epiblast under defined culture conditions, including the presence of FGF2 and activin, and they can be induced to revert to the mESC-like state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, both cell types are maintained by the same extrinsic signals, namely, activin/ nodal and FGF2 signaling. Recent studies have demonstrated that EpiSCs, which are more advanced developmentally than mESCs, can be induced to revert to mESC-like cells [41,42,[49][50][51]. FAB-SCs are generated from the preimplantation epiblast under defined culture conditions, including the presence of FGF2 and activin, and they can be induced to revert to the mESC-like state.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that LIF/STAT3 signaling contributes to the reversion of primed state EpiSCs to naïve state mESCs [49,50]. Additionally, a recent study showed that weak transduction of the LIF/STAT3 signal is a possible barrier to this reversion [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second series of studies, similar dedifferentiation from an EpiSC to an ICM-like state was accomplished by supplementing standard mESC medium, containing leukemia inhibitory factor (LIF), with small molecules targeting epigenetic modifiers and/or signaling pathways differentially used by the two pluripotent cell types [19,20]. Moreover, Bao et al [21] demonstrated that EpiSC derived from E5.5 to E7.5 embryos could spontaneously revert to an ICMlike ground state when cultured for 14-35 days on MEFs supplemented with LIF but without any other factors. The reverted ESC could generate germline-competent chimeras and progressively lost the histone 3 lysine 27 trimethylation (H3K27me3) mark on the inactive X chromosome, which was associated with loss of X-chromosome silencing.…”
Section: Culture Mediated Alterations In Fate Of Pluripotent Cellsmentioning
confidence: 99%
“…Gene expression analysis indicates shared expression of Oct4 and SSEA1 but differential expression of a group of genes, including Stella, Rex1, Pecam1, Gbx2, and Fgf5 (Bao et al, 2009;Brons et al, 2007;Tesar et al, 2007). Differential expression of GFP by Oct4 regulatory sequences can be used to distinguish the two different pluripotent states (Han et al, 2010a;2010b).…”
Section: Choice Of Pluripotent Statesmentioning
confidence: 99%